LIFE AND WORK OF THEODORE DREISER AND HIS IMPACT ON THE WORLD LITERATURE. - Sadikova, Saodat (Журнал иностранных языков и лингвистики, 2021)
This article is about the famous American writer, publisher, and public figure Theodore Dreiser. He made a huge contribution to the development of American culture and world literature. Many people specifically study English in order to read his works without translation. Most of his famous novels were translated into Uzbek language and Uzbek nation read his work with great enthusiasm